A decade in diabetes specialist services, 2000 to 2011, in England: the views of consultant diabetologists and diabetes specialist nurses amidst persistent healthcare delivery change. Issue 12 (16th May 2015) - Gosden, C. A.; Barnard, K.; Williams, D. R. R.; Tinati, T.; Turner, B.; Holt, R. I. G.
Abstract: Aims: To assess the impact of continual major National Health Service reorganization on commissioning, organizational and delivery arrangements for secondary care diabetes services. To explore how consultant diabetologists and diabetes specialist nurses perceive the issues facing diabetes specialist services in 2011 and how these have changed in the preceding decade. Methods: We used a longitudinal case study approach that combined quantitative and qualitative methods. Five locations in England were purposively selected to represent the wider diabetes specialist community, and seven semi‐structured interviews were conducted. Interviews were recorded, transcribed verbatim and analysed using Framework analysis. Findings were compared with and contrasted to results from national quantitative surveys of diabetes specialist services undertaken in 2000 and 2006. Results: Clinicians viewed positively the expertise and commitment of multidisciplinary teams and their ability to adapt to new situations. Negative perceptions persisted throughout the decade, relating to the continual change that threatens to dismantle relationships and services which had taken many years to establish. Lack of resources, inadequate manpower planning and poor access to psychological support for people with diabetes remained constant themes from 2000 to 2011. Conclusions: A willingness to innovate and work differently to improve services was identified; however, clinicians must be supported through organizational changes to ensure people with diabetes receive high‐quality care. The disruptive nature of organizational change was a recurrent theme throughout the decade. Periods of stability must exist within commissioning to allow relationships, which are key to integration, to be maintained and permit service improvements to develop. What's new?: Continual National Health Service redesign and commissioning change has had a negative impact on the morale of clinicians in stretched specialist services with fewer resources. Concern was expressed that those commissioning services had not understood the complexity of diabetes and manpower requirements. Access to psychological support for people with diabetes remained poor. There was optimism for the role of specialist teams within increasingly specialist tertiary services, willingness to work in partnership and lead development of integrated services. The study used an innovative methodological approach combining quantitative and qualitative tools in a longitudinal case study design, investigating the views of healthcare professionals.